Down-Modulation of Programmed Death 1 Alters Regulatory T Cells and Promotes Experimental Autoimmune Encephalomyelitis - Wang, Chunhe (2010)
The regulatory role of programmed death 1 (PD-1) was investigated in the development of experimental autoimmune encephalomyelitis (EAE), an animal model of multiple sclerosis. Typical EAE could be induced by immunization without pertussis toxin (PTX) in PD-1-null but not in wild-type (WT) mice. However, both strains developed a similar EAE phenotype when immunized with PTX or by adoptive transfer of pathogenic T cells. In WT mice that did not develop EAE after immunization without PTX, the frequency of CD4(+)FoxP3(+) Treg cells was boosted in the periphery but not in the thymus. This increase in Treg frequency was abrogated by PD-1 deficiency or inclusion of PTX. In addition, PD-1 expression was critical to in vitro conversion of naïve myelin-specific CD4 T cells into Treg cells and was directly related to Treg suppressive activity. Finally, PD-1 was markedly down-modulated in the periphery of WT mice after administration of PTX. Therefore, down-modulation of PD-1 in Treg cells may abrogate Treg-mediated immune suppression, permitting the activation of myelin-reactive T cells and induction of EAE.